Perancangan Sistem Informasi Online Self service Perpustakaan Universitas Muhammadiyah Magelang - Astianto, Dwi; Fatimah, Yun Arifatul; Pujiarto, Bambang (Jurnal Komtika (Komputasi dan Informatika), 2020)
Library systems of Muhammadiyah University of Magelang still uses manual way for the borrowing, renewals and returns processes, so it takes a long time to get information needed. Therefore, it needs adequate library information system for the automatic borrowing, repayment, and borrowing requests processes which produces information quickly and accurately. This research aimed to design an online Self service information system for procces in the library of Muhammadiyah University of Magelang. This system uses the online Self service for the book reservation and book extension process. Self service on this study is in the transaction book service, because the system is able to record borrowing transaction data automatically after the lending process is completed. Thus it is not necessary to input the data manually by officers transaction. This research is able to make a reservation and extension system of books online. In addition the borrowing transactions will be automatically recorded if the user uses the system. The conclusions obtained from this study is the borrower will be easier to borrow and renew online. In addition, the system can also allow officers to keep the records of transactions and to monitor the books on library Muhammadiyah University of Magelang